Pelatihan Hatha Yoga Bagi Lansia Di Banjar Jurang Asri Desa Peguyangan Kangin Kecamatan Denpasar Utara Kota Denpasar - Sumarkandia, Wayan (Universitas Ngurah Rai, 2023)
Health problems are one of the problems in society, especially for the elderly. In this case, Hatha Yoga training is seen as very important in efforts to improve physical and spiritual health for the community, especially the elderly in Banjar Jurang Asri, Peguyangan Kangin Village, North Denpasar District, Denpasar City. This research took the form of a qualitative design. Data was collected using observation techniques, interview techniques and library techniques. After the data was collected, the data was analyzed using qualitative descriptive and interpretative descriptive methods. Based on this analysis, conclusions were obtained as a result of the research, as follows: (1) The process of implementing hatha yoga training consists of opening greetings and group prayers, pranayama exercises, warm-up movements, hamsa, surya namaskara exercises, loose asanas, Savasana, meditation, hasya yoga and cover. (2) The function of hatha yoga training consists of functions for physical fitness and functions for spiritual depth. (3) the implications of hatha yoga training consist of implications for life behavior, implications for social behavior and implications for spiritual behavior.